Assessment of imaging dose from the kilovoltage cone beam computed tomography system on board the Varian Halcyon linear accelerator - Mbewe, Jonathan (Division of Radiology, 2025)
Daily cone-beam computed tomography (CBCT) is mandatory for cancer patients receiving radiotherapy treatment using advanced techniques on the Varian Halcyon linear accelerator for setup verification, correction, and adaptation of the treatment plan. The frequent nature of imaging sessions mostly using kilovoltage (kV) x-ray energies has raised concerns about the contribution of low-energy radiation dose to the overall integral dose and possible induction of secondary primary tumours. In this study, the dose to organs and tissues located in the pelvic and thoracic regions of the body from kV CBCT imaging was estimated using the GATE Monte Carlo toolkit. The spectral, dose output, and filtration characteristics of the x-ray source on the Halcyon kV CBCT system were derived through measurements using a calibrated ionisation chamber and analytical calculations. The outcomes of this process were used to build a geometry for the Monte Carlo model of the beamline, and then validate it by comparing the computed Percentage Depth Dose and Crossline profiles to those measured in a water phantom using calibrated parallel plate and thimble ionisation chambers. In-phantom dose measurements using Radiochromic film in RANDO pelvic and thoracic phantoms were used to generate a Normalisation Factor to relate the measured and simulated absorbed doses. To estimate the patient doses, Monte Carlo simulations were performed on the Adult Female reference computational phantom from the International Commission for Radiation Protection (ICRP) publication 110. The highest doses to the pelvic region resulted from the “Pelvis Large” imaging protocol, with organ doses ranging from 5.11 mGy to 174.96 mGy per CBCT scan. In the thoracic region, the “Thorax” protocol resulted in the highest doses, ranging from 2.75 mGy to 54.63 mGy per CBCT scan. Depending on the fractionation regimen in use, there is a possibility that the imaging doses may exceed 5% of the prescribed therapeutic dose, in which case the imaging dose may need to be added to the treatment plan per recommendation of the AAPM Task Group 180 report.